Survey of Potyviruses, Carlaviruses, and Begomoviruses in Potato Cultivation Centers of West, Central, and East Java Provinces, Indonesia - Adyatma Irawan Santosa; Rossa Wulandari; Meyrin Novia Vadilah; Erlin Sabila; Asista Fatma Kusuma; Dedi Mulyadi; Intan Berlian; Made Getas Pudak Wangi; Ade Mahendra Sutejo; Ali Çelik (International Journal of Plant Biology)
Our knowledge of the molecular data on viruses infecting potato (Solanum tuberosum) and its weeds in Indonesia still needs to be expanded. Thirteen potato leaves, together with one carrot (Daucus carota subsp. sativus) and one Oxalis latifolia leaves grew adjacent to potato fields were sampled in West, Central, and East Java Provinces of Indonesia to be tested using RT-PCR with universal primers to monitor the presence of potyviruses, carlaviruses, and begomoviruses in the surveyed regions. According to the test results and BLAST nucleotide analysis, four potato samples were found to be infected by potato virus Y (PVY, Potyvirus). All samples tested negative for carlaviruses and begomoviruses. Both phylogenetic trees constructed by MEGA11 software based on partial coat protein and partial coat protein + 3′-UTR sequences demonstrated that the four new PVY isolates belong to strain N. Nucleotide and amino acid homology analysis determined that all four new and 12 other strain N isolates registered in NBCI GenBank were identical at the observed genome region, suggested the same origin of Indonesian isolates. This study improved our understanding of the variation in PVY isolates in Indonesia and highlighted the need for tight surveillance since the country imports most of its tubers used as planting material.